High‐resolution microbiota flow cytometry reveals dynamic colitis‐associated changes in fecal bacterial composition. Issue 5 (May 2016) - Zimmermann, Jakob; Hübschmann, Thomas; Schattenberg, Florian; Schumann, Joachim; Durek, Pawel; Riedel, René; Friedrich, Marie; Glauben, Rainer; Siegmund, Britta; Radbruch, Andreas; Müller, Susann; Chang, Hyun‐Dong
Abstract : Using high‐resolution flow cytometry of bacterial shape (forward scatter) and DNA content (DAPI staining), we detected dramatic differences in the fecal microbiota composition during murine colitis that were validated using 16S rDNA sequencing. This innovative method provides a fast and inexpensive tool to interrogate the microbiota on the single‐cell level.